2020
DOI: 10.3389/fmicb.2020.550420
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of Environmental Microbial Community Studies Are Biased by the Selected 16S rRNA (Gene) Amplicon Sequencing Pipeline

Abstract: Straub et al. 16S rRNA (Gene) Amplicon Analysis starting from raw sequence files, using the most optimal methods identified in our study. Our presented workflow should be considered for future studies, thereby facilitating the analysis of high-throughput 16S rRNA (gene) sequencing data substantially, while maximizing reliability and confidence in microbial community data analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 96 publications
6
96
0
1
Order By: Relevance
“…Statistical analysis (Wilcoxon signed-rank test) was performed at a depth of (A: qI) 29,998 and (B: qII) 30,000. Double asterisks indicate statistical significance (p < 0.01) DADA2 is used for ASV clustering and does not output unassigned ASVs, in contrast to OTU clustering with qI, and is reported to be superior in sequence clustering ability [32,36,37]. Our results indicated that the V34 results contain more filtered-out sequences that would be excluded when processed by DADA2, which clusters ASVs more accurately.…”
Section: Discussionmentioning
confidence: 80%
“…Statistical analysis (Wilcoxon signed-rank test) was performed at a depth of (A: qI) 29,998 and (B: qII) 30,000. Double asterisks indicate statistical significance (p < 0.01) DADA2 is used for ASV clustering and does not output unassigned ASVs, in contrast to OTU clustering with qI, and is reported to be superior in sequence clustering ability [32,36,37]. Our results indicated that the V34 results contain more filtered-out sequences that would be excluded when processed by DADA2, which clusters ASVs more accurately.…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, we reconstructed RF models with the same hyperparameters as the discovery RF models. Considering the limited resolution of the 16S rRNA gene and incomplete reference database 53 , not all ASVs could be assigned at the species level. Thus all ASVs with the same taxonomy assignments (at genus level), as well as patient metadata (only used ASVs for validation cohort2 for lack of the patient metadata), were used as the input features.…”
Section: Methodsmentioning
confidence: 99%
“…Data with clean reads were analyzed by using the nf-core/ampliseqv1.2.0 pipeline, and the microbial diversity within our datasets were determined by setting the optional parameters “- -multiple Sequencing Runs,” “- -trunclenf 220,” and “- -trunclenr 180” (to resemble the truncation values of QIIME2 with DADA2) ( Straub et al, 2020 ). The 16s rRNA gene comparison database, SILVA v132 ( Quast et al, 2013 ), was used to perform clustering at 99% similarity.…”
Section: Methodsmentioning
confidence: 99%